2016
DOI: 10.1002/bmb.20961
|View full text |Cite
|
Sign up to set email alerts
|

Metadiscourse markers in biological research articles and journal impact factor: Non‐native writers vs. native writers

Abstract: Metadiscourse markers (MDMs) are lexical resources that writers employ to organize their discourse and state their stance towards the content or the reader. This study investigated the frequency with which interactive and interactional MDMs were employed in biological research articles (RAs). It also explored the possible relationship between the frequency of these markers and Impact Factor (IF) of journals as an index of quality. Moreover, it aimed at finding out the difference(s) between two groups of author… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…T-test results revealed that Arab researchers of English Articles (NNSs) differ in terms of the amount of metadiscourse devices used in Scientific Research Articles from English researchers of English articles and therefore differ in their level of proficiency from English researchers (NSs). These findings are consistent with those reported in previous studies (Khedri, & Konstantinos, 2018;Gholami, & Ilghami, 2016;Keshavarz, & Kheirieh, 2011). For example, consistent with the finding of this study Khedri, and Konstantinos (2018) observed differences in metadiscourse devices applied in introductory sections of chemistry…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…T-test results revealed that Arab researchers of English Articles (NNSs) differ in terms of the amount of metadiscourse devices used in Scientific Research Articles from English researchers of English articles and therefore differ in their level of proficiency from English researchers (NSs). These findings are consistent with those reported in previous studies (Khedri, & Konstantinos, 2018;Gholami, & Ilghami, 2016;Keshavarz, & Kheirieh, 2011). For example, consistent with the finding of this study Khedri, and Konstantinos (2018) observed differences in metadiscourse devices applied in introductory sections of chemistry…”
Section: Discussionsupporting
confidence: 94%
“…International Journal of Linguistics ISSN 1948-5425 2019 and applied linguistic research articles by native speakers of English and native speakers of English. Similarly, Gholami, and Ilghami (2016) found that native writers (American writers) and non-native English writers (Iranian writers) of biological research articles significantly differ in the frequency of interactional and interactive metadiscourse devices confirming that natives are significantly more proficient in English than non-natives in writing scientific research articles. In particular, Gholami, and Ilghami (2016) confirmed that native English writers employ significantly more interactional and interactive in scientific articles than non-native writers.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This study looked only at RAs and not other types of MSs (Rezaee & Sayfouri, ). These articles commonly use the IMRAD structure ( Introduction , Method , Results and Discussion ) (Gholami & Ilghami, ). To establish consistency in our analysis, articles with a separate conclusion were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
“…Due to its importance, metadiscourse markers have been investigated in various genres including research articles (e.g. Abdi 2009, Afros & Schryer 2009, Dahl 2004, Gillaerts & Van de Velde 2010, Gholami & Ilghami 2016, Mur-Dueñas 2011, students' writings (e.g. Cheng & Steffensen 1996, Crismore, Markkanen & Steffensen 1993, Hyland 2004a, Intaraprawat & Steffensen 1995, textbooks (e.g.…”
Section: Introductionmentioning
confidence: 99%